MOTIVASI TERHADAP TINGKAH LAKU DALAM PROSES DAKWAH - Nawawi Nawawi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Da’wa activity is aimed at influencing people to do certain behaviour. Forthis reason, it needs to apply psychological approach. By applying this approach, any da’wa activity must consider the need of people who become its target. A da’i should be able to motivate his targets to do certain behaviour as he expects.